VIEWS OF THE MANIFESTATIONS OF THE ENLIGHTENMENT AND THE JADIDISM MOVEMENT ON THE PATH TO HUMAN SPIRITUAL PERFECTION - Salamov Khurshid Bariddinovich (American Journals, 2024)
This article describes the socio-political foundations and historical conditions of the emergence of the Enlightenment and Jadidism movements, the views of the representatives of the Enlightenment and Jadidism movements on the path of spiritual perfection of man. The spiritual heritage of thousands of brave warriors who died innocently in the difficult times that befell our people, the realization of national identity, independence of our country, the foundations of todayʻs peaceful and peaceful life are studied.
Keywords: Renaissance, enlightenment, spirituality, knowledge, science, enlightenment, school, education, past, generation, literature, injustice, religion, corruption.